Menguji Validitas Asas Praduga Tidak Bersalah Terhadap Tersangka Tindak Pidana terorisme - Taufik, Iqbal; Muammar (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
This study aims to determine the validity of the presumption of innocence principle against perpetrators or suspected perpetrators of criminal acts of terrorism committed by law enforcement officials, especially Densus 88. This paper uses a statute approach and a conceptual approach. The results showed that the principle of presumption of innocence in handling criminal acts of terrorism is, in fact, still often ignored by law enforcement officials. Even the data obtained shows that several suspects/perpetrators have died during the legal process they underwent, as well as the actions of law enforcement officials who often commit acts that exceed limits and violate human rights. This principle needs to be implemented and strictly regulated in the Criminal Procedure Code as the master procedural law as well as in the law on the eradication of criminal acts of terrorism so that the strength and application of this principle increasingly get a place and position that can protect perpetrators/suspected perpetrators of criminal acts of terrorism.